FILSAFAT DAN MANAJEMEN - Yosal Iriantara, Yosal Iriantara; Reni, Reni; In In Indriani, In In Indriani; Rise Meilani, Rise Meilani (Wali Pikir: Journal Of Education, 2024)
All knowledge cannot be separated from philosophy, because philosophy itself is the root of all human knowledge, both scientific and non-scientific. Philosophy and management science are closely related. Practice and management science have a very deep philosophical dimension. Management cannot be separated from philosophy because without philosophy, management does not have a strong foundation. Without management, philosophy will only be knowledge that has not been practiced. This paper aims to describe the philosophy of management science philosophically through the perspectives of ontology, epistemology and axiology. The ontological perspective in management science is the existence of a reality in human life. The epistemological perspective in management science is related to the scientific method approach that can be taken to solve the problem. And, the axiological perspective understands the values contained or implied and we can express them.